Covalent organic frameworks for photocatalysis: Synthesis, structural features, fundamentals and performance - Gong, Yun-Nan; Guan, Xinyu; Jiang, Hai-Long (Coordination chemistry reviews, 2023)
Covalent organic frameworks (COFs), constructed by organic building blocks through strong covalent bonds, featuring well-defined structures, excellent stability and desired semiconductor-like behavior, have been employed for extensive potential applications, especially in photocatalysis. In this review, we summarize the different methods for the synthesis of COFs, such as solvothermal synthesis, microwave synthesis, ionothermal synthesis, room temperature solution synthesis, mechanochemical synthesis and interfacial synthesis firstly. Then, the structural features of COFs such as diversity, tailorability, stability and porosity. Whereafter, the advantages and fundamentals of COFs in photocatalysis are introduced. Furthermore, the photocatalytic applications of COF-based materials toward H2 production, CO2 reduction, organic transformation and pollution degradation are discussed. Particularly, diverse strategies for improving photocatalytic performance and the corresponding structure-activity relationships are highlighted. Finally, the challenges and future prospects for the development of efficient COF-based photocatalysts are briefly indicated. [Display omitted] •An overview of the introduction of different methods for the synthesis of COFs.•The structural features of COFs including diversity, tailorability, stability and porosity.•The advantages and fundamentals of COFs in photocatalysis.•Photocatalytic applications of COF-based materials in the fields of H2 production, CO2 reduction, organic transformation and pollution degradation.•The challenges and opportunities for the development of COF-based photocatalysts. Covalent organic frameworks (COFs) are a new class of crystalline porous materials obtained from covalently attached organic building units. By virtue of the unique characteristics such as periodic and well-defined structures, low-density, high surface area, excellent stability as well as desired semiconductor-like behavior, COFs have gained tremendous attention for functional applications in many fields, especially in photocatalysis. In this review, we summarize the different methods for the synthesis of COFs, such as solvothermal synthesis, microwave synthesis, ionothermal synthesis, room temperature solution synthesis, mechanochemical synthesis and interfacial synthesis firstly. Then, the structural features of COFs including diversity, tailorability, stability and porosity are provided. Afterwards, the fundamentals and advantages of COFs for photocatalysis are briefly introduced. Following this, the photocatalytic applications of COF-based materials toward H2 production, CO2 reduction, organic transformation and pollution degradation are discussed. Meanwhile, a series of strategies are highlighted to improve photocatalytic performance for the understanding of the structure-property relationship in this part. Finally, the remaining challenges and prospects on further development of efficient COF-based photocatalysts are indicated.